Challenges Of Communication System During Emergency Disaster Response In Malaysia: A Review - Azmani, S; Juliana, N; Idrose, AM; Amin, NA; Saudi, ASM (Univ El Oued, Fac Science & Technology, 2024)
Indexed by WOS